Desmond Tutu, symbol of a prophetic theology - Márquez Beunza, Carmen (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
Anglican archbishop Desmond Tutu is one of the most prominent and representative leaders in South African Churches. This article explores his life, theology and church ministry. It highlights his role in the struggle against apartheid and his contribution to the process of national reconciliation as the chairman of the Truth and Reconciliation Commission.